The use of wood during prehispanic times in the Upper Paraná Delta revealed though analysis of ancient charcoal - Ramos, Rita Soledad (2021)
Woody plant resources are important to human societies today and were also in the past. Here we assess the woody plant resources available to peoples in Northeastern Argentina in the pre-Hispanic period and assess how they were used. The Upper Parana Delta (Entre Rios province, Argentina) was occupied by indigenous societies during the last 2000 years, and evidence of those peoples has been found at Los Tres Cerros 1 archaeological site (inhabited at least between 765 to 1505 cal years AD). From the local traditional and ethnographical literature, a broad functionality of the determined taxa is proposed, to use as a basis for palaeoethnobotanical interpretations. Species of the Lauraceae, Passifloraceae, Fabaceae, Salicaceae, Boraginaceae and Apocynaceae families were found dispersed about the site; they possibly grew close to the settlement and had diverse indigenous uses (e.g. for the construction of canoes and other artefacts in daily use). Other species were found concentrated on the archaeological site. They were related to Euphorbaceae, Fabaceae, Cyperaceae, Anacardiaceae, Apocynaceae, Myrtaceae and Primulaceae and were probably used as fuel in domestic activities (e.g. to obtain light, heat and to cook food and fire pottery). Forty-three carbonized wood samples were studied. Charcoals related to Sapium, Nectandra and Aspidosperma genera were identified next to pottery and animal bones. The presence of Schinopsis in the anthracological record shows the extra-local link of the pre-Hispanic populations that occupied the Parana river basin. Finally, these new advances increase the knowledge about the vegetation nearby the archaeological site at the end of the Late Holocene.